A study to assess the completeness of informed consent documents for biomedical research on human participants submitted to the institutional ethics committee of a tertiary care hospital - Anandabaskar, Nishanthi; Vimal, Mourouguessine; Dongre, Amol Rambhau; Kagne, Rajendrakumar Nivaratirao (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Informed consent is an essential pre-requisite for research on human participants. However, many studies have shown that informed consent documents (ICDs) are incomplete and lack many of the essential elements. The objective of the study was to assess the completeness of ICDs submitted to an institutional ethics committee (IEC) against the Indian Council of Medical Research (ICMR) ethical guidelines for biomedical research on human participants. Methods: This is a retrospective cross-sectional study. The ICDs submitted to the IEC during the period from January 2015 to December 2017 were reviewed for completeness, with the help of a checklist which is based ICMR ethical guidelines for biomedical research on human participants 2006. Results: A total of 212 ICDs were reviewed during the study period. More than 50% of the ICDs have clearly explained many of the essential elements like nature and purpose of the study (62.3%), voluntary participation (98.6%), procedures (68.9%), risks (71.2%), benefits (92.9%), alternative treatments (60.7%), maintaining confidentiality (99.1%), no loss of benefits on withdrawal from the study (87.8%) and contact details of principal investigator (99.5%). However, the other essential elements of the ICD are either not mentioned or not clearly explained. Conclusions: This study has shown that although majority of the ICDs submitted for review by the IEC have mentioned many of the essential elements, some of the elements like contact details of Chairman of IEC, future use of sample, compensation for trial related injury and provision of counseling for consent of genetics testing have not been stated.